What Lies behind the Returns to Schooling: The Role of Labor Market Sorting and Worker Heterogeneity - Portugal, Pedro; Reis, Hugo; Guimarães, Paulo; Cardoso, Ana Rute (The Review of Economics and Statistics, 2024)
Do more educated workers earn higher wages partly because they have access to high-paying firms and occupations? We rely on linked employer-employee data to combine the estimation of AKM models with the decomposition of the returns to schooling. We exploit exogenous variation in education driven by changes in compulsory education. We show that education provides access to better-paying workplaces and occupations: 30 percent of the overall return to education operates through the workplace channel and 12 percent through the occupation channel. The remainder is associated exclusively with the individual. Match quality plays a modest role in the returns to education.